Antioxidant Capacity and Î±-Amilase Inhibition by Avocado (Persea americana Mill) Peel and Red Ginger (Zingiber officinale var. Rubrum) based Functional Drink - I Made Wisnu Adhi Putra; Ketut Ayu Sukesi; Ni Putu Eny Sulistyadewi (Chemistry Education Program, the University of Mataram, 2020)
Avocado peel (Persea americana Mill) and red ginger (Zingiber officinale var. Rubrum) proved to have antidiabetic properties. However, there has been no research on the analysis of antidiabetic activity of the combination of avocado peel and red ginger in functional beverages. This study aims to make functional beverages from the combination of avocado peel and red ginger. Total phenolic content, antioxidant capacity, inhibition of the Î±-amylase activity, and public preferences towards functional beverages (organoleptic) were then evaluated. Functional beverages were made by brewing the powdered avocado peel and red ginger with 200 ml of hot water (96oC) for 5 minutes. The results showed that the increase of avocado peels amount in the combination coukd increase total phenolic content. The high antioxidant capacity was also found in samples with high content of avoccado peels. The results of inhibition of Î±-amylase enzyme activity did not show any significant differences. Organoleptic test results showed that there were no significant differences in each sample. The combination of avocado peel and red ginger has the potential to be an antidiabetic functional beverage.